(untitled) (Altre Modernità, 2022)
The small island of Lampedusa, a key destination of the Central Mediterranean Route connecting Africa to Italy, offers a special observatory on the contemporary trans-Mediterranean odyssey of migrants, although often transformed into a “border spectacle.” Upon landing, migrants are stripped of their belongings, as these are impounded by the authorities. Such an act of dispossession is intended to deprive them of their histories, family ties and cultural identity. Photographer Mario Badagliacca has portrayed a selection of these lost and retrieved items in his work Fragments (2013). Each object reveals expectations, fears, desires, endurance, but cannot tell a full story. They are fragments of an open-ended narrative that requires to be framed and told, if we wish to gain a better understanding of the Black Mediterranean, its history, and consequences. What remains untold can only be imagined. Writer Maaza Mengiste imagines what lies behind two smudged photographs portrayed by Badagliacca. As always, the force of imagination provides signification, solidarity, and survival in the fractured history of the African Diaspora.